The Mediating Effect of Work Stress on the Relationship Between Intellectual Intelligence and Spiritual Intelligence and Nurse Performance (Study at PKU Muhammadiyah Hospital Sukoharjo) - Intan Sari Mahardika; Muchlis Mas’ud; Ana Sopanah (LPPM Institut Teknologi dan Sains Mandala, 2025)
Nurse performance plays a vital role in determining the quality of healthcare received by patients. Intellectual intelligence and spiritual intelligence are among the factors that can influence performance. Job stress can also impact nurse performance. This study uses a quantitative approach with an explanatory research approach to analyze the influence of intellectual intelligence and spiritual intelligence on nurse performance, with job stress as a mediating variable. This study aims to obtain empirical evidence regarding the relationship between these variables, both partially and simultaneously. Overall, it can be concluded that in this study, intellectual intelligence and spiritual intelligence play an important role in influencing job stress, but do not directly improve employee performance. Furthermore, job stress itself has not been shown to have a significant direct impact on employee performance. These findings indicate the need for further study of other variables that may play a greater role in influencing performance.